2008
DOI: 10.1007/s11199-007-9367-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment Mythology: Definition, Conceptualization, and Measurement

Abstract: Using rape myth research as a template, we developed a conceptual definition and measurement instrument for the mythology regarding male sexual harassment of women, resulting in the 20-item Illinois Sexual Harassment Myth Acceptance (ISHMA) Scale. Surveys from 337 students in the Midwestern region of the United States revealed that this measure consists of four factors, which share predicted relationships with rape mythology, sexism, hostility toward women, traditional attitudes toward women, and ideological s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
149
1
15

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(180 citation statements)
references
References 59 publications
(89 reference statements)
15
149
1
15
Order By: Relevance
“…Faced with a situation of unwanted sexual attention, most participants thought the woman would perceive herself as coming closer to fitting a man's image of an ideal partner, and the woman would see herself as being seen by John as provocative, regardless of the type of victim response to the incident of harassment. This highlights the influence of myths in the perception and evaluation of events (Lonsway et al, 2008), given that myths modulated the image women had of themselves, and what was expected of them. Similar results have been reported for other types of violence against women, which underscores that attitudes to gender violence are crucial for understanding reactions and behaviours towards victims and harassers (Gracia, García, & Lila, 2009).…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Faced with a situation of unwanted sexual attention, most participants thought the woman would perceive herself as coming closer to fitting a man's image of an ideal partner, and the woman would see herself as being seen by John as provocative, regardless of the type of victim response to the incident of harassment. This highlights the influence of myths in the perception and evaluation of events (Lonsway et al, 2008), given that myths modulated the image women had of themselves, and what was expected of them. Similar results have been reported for other types of violence against women, which underscores that attitudes to gender violence are crucial for understanding reactions and behaviours towards victims and harassers (Gracia, García, & Lila, 2009).…”
Section: Discussionmentioning
confidence: 84%
“…Several studies have observed how myths of violence against women, e.g., on sexual assault, serve to deny, trivialize, and justify patriarchal violence against women (Gerger, Kley, Bohner, & Siebler, 2007;Herrera et al, 2014;Herrera, Herrera, & Expósito, 2016). These myths include beliefs and behaviours that blame the victim, minimize the psychological impact on victims, and justify the behaviour of the harasser (Lonsway et al, 2008). All of these myths are designed to raise harassment tolerance levels; consequently, they have negative repercussions on victims and hinder the recovery process (Campbell, Wasco, Ahrens, Sefl, & Barnes, 2001), and reduce the chances victims will report incidents of harassment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lonsway, Cortina, and Magley (2008) identified similar beliefs supporting sexual harassment; although they identify slightly different examples, the functional similarity is clear: to deny the reality of what is happening and to justify it when denial is no longer possible.…”
mentioning
confidence: 96%